FEATURES OF THE STUDY OF MORBIDITY IN THE CENTRAL MILITARY CLINICAL HOSPITAL - Jakbarova M.A; Juraeva M.A (Scholar Express Journals, 2023)
analysis of the incidence of the military in this article; identification and assessment of the leading risk factors for chronic non infection diseases; identification and assessment of the features of the clinical course of chronic non infection diseases among the military; separation and comparative assessment of priority risk factors that negatively affect the development and clinical course of chronic non infection diseases among the military; among the military, the development of an improved effective technology for the early detection and Prevention of chronic non-infectious diseases and the introduction into practice as an experiment took an innovative approach
Keywords: early detection of diseases; non-infectious diseases; accompanied by cashlessness in the military